Life History of Aricoris propitia (Lepidoptera: Riodinidae)—A Myrmecophilous Butterfly Obligately Associated with Fire Ants - Lucas A. Kaminski; Fernando S. Carvalho-Filho (Psyche: A Journal of Entomology)
The immature stages of Aricoris propitia (Stichel) are described and illustrated for the first time, using both light and scanning electron microscopy. Females oviposit in at least seven host-plant families, always in the presence of fire ants (Solenopsis saevissima (Smith) complex), without being attacked by them. Larvae are tended by ants during all larval and pupal stages. From the fourth instar on, larvae feed at night and rest during the day inside underground shelters constructed by ants on the host plant roots, and where pupation occurs. Several observed features, including ant-mediated oviposition, persistent ant attendance throughout all instars, and high spatiotemporal fidelity indicate that A. propitia is a myrmecophile obligately associated with fire ants. We propose A. propitia as an extraordinary model for studies on ant-butterfly evolutionary history in the Neotropics.